2021
DOI: 10.1038/s41419-021-04344-w
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional inhibition by CDK7/9 inhibitor SNS-032 suppresses tumor growth and metastasis in esophageal squamous cell carcinoma

Abstract: Metastasis is one of most lethal causes that confer a poor prognosis of patients with esophageal squamous cell carcinoma (ESCC), whereas there is no available target drug for metastatic ESCC currently. In this study, we aimed to determine whether the transcriptional inhibition by CDK7/9 inhibitor SNS-032 is activity against ESCC. MTT and soft agar assays were performed to examine the influence of SNS-032 on ESCC growth in vitro. Tumor xenograft in nude mice was used to assess the antitumor activity of SNS-032 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…In this study, we found that SNS-032 significantly downregulated the expression levels of Bcl-2, XIAP, and Mcl-1 ( Figure 4 ). However, some previous studies on other cell types found that SNS-032 has no major effects on the protein levels of XIAP and Bcl-2 ( Zhang et al, 2019 ; Zeng et al, 2021 ). In our opinion, given that different cell lines undergo different transformations, the regulatory effects of SNS-032 may vary across different cell lines.…”
Section: Discussionmentioning
confidence: 89%
“…In this study, we found that SNS-032 significantly downregulated the expression levels of Bcl-2, XIAP, and Mcl-1 ( Figure 4 ). However, some previous studies on other cell types found that SNS-032 has no major effects on the protein levels of XIAP and Bcl-2 ( Zhang et al, 2019 ; Zeng et al, 2021 ). In our opinion, given that different cell lines undergo different transformations, the regulatory effects of SNS-032 may vary across different cell lines.…”
Section: Discussionmentioning
confidence: 89%
“…The wounded area was recorded using an inverted phase-contrast microscope. The wound-healing rate was calculated as: ([wound width at 0 h − width at 24 h]/width at 0 h) × 100% 16 .…”
Section: Methodsmentioning
confidence: 99%
“…The cells were treated with above method ( Measurement of Glucose Uptake ) for 48 h later, Western Blot was carried out according to the reference ( 22 ).…”
Section: Methodsmentioning
confidence: 99%